2021
DOI: 10.1093/nar/gkab277
|View full text |Cite
|
Sign up to set email alerts
|

A nucleotide-sensing endonuclease from the Gabija bacterial defense system

Abstract: The arms race between bacteria and phages has led to the development of exquisite bacterial defense systems including a number of uncharacterized systems distinct from the well-known restriction-modification and CRISPR/Cas systems. Here, we report functional analyses of the GajA protein from the newly predicted Gabija system. The GajA protein is revealed as a sequence-specific DNA nicking endonuclease unique in that its activity is strictly regulated by nucleotide concentration. NTP and dNTP at physiological c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 42 publications
3
75
0
Order By: Relevance
“…Similarly, OLD is the archetypical member of a family of ABC-ATPases fused to a TOPRIM nuclease domain that is found in diverse defense contexts ( Aravind et al, 1998 ; Krishnan et al, 2020 ). In combination with a UvrD-family helicase and RNAseH-family exonuclease, OLD is part of a widespread system that provides cells with innate immunity against several distinct bacteriophages ( Doron et al, 2018 ; Cheng et al, 2021 ). The old and fun superinfection exclusion genes are just two examples of innate immune systems found in prokaryotic genomes associated with mobile genetic elements ( Makarova et al, 2013 ), reflecting a broad evolutionary pattern of continuous back and forth gene shuffling.…”
Section: Mainmentioning
confidence: 99%
“…Similarly, OLD is the archetypical member of a family of ABC-ATPases fused to a TOPRIM nuclease domain that is found in diverse defense contexts ( Aravind et al, 1998 ; Krishnan et al, 2020 ). In combination with a UvrD-family helicase and RNAseH-family exonuclease, OLD is part of a widespread system that provides cells with innate immunity against several distinct bacteriophages ( Doron et al, 2018 ; Cheng et al, 2021 ). The old and fun superinfection exclusion genes are just two examples of innate immune systems found in prokaryotic genomes associated with mobile genetic elements ( Makarova et al, 2013 ), reflecting a broad evolutionary pattern of continuous back and forth gene shuffling.…”
Section: Mainmentioning
confidence: 99%
“…We propose a model where NixI functions as a nicking endonuclease, introducing site-specific nicks into ICP1's genome. Anti-phage defense systems that encode nicking endonucleases have recently been characterized suggesting nicking is an effective strategy to destroy invading viral DNA (32,53). We show here that NixI is the most inhibitory PLE-encoded product characterized thus far, inhibiting ICP1 progeny production to the same extent as is seen with PLE, and reducing ICP1 replication by an order of magnitude.…”
Section: Discussionmentioning
confidence: 65%
“…As HNH nucleases require a divalent metal co-factor for activity (typically magnesium, manganese or zinc (28-31)), we investigated NixI's metal requirement with a panel of divalent metals at differing concentrations and determined NixI can utilize Mg 2+ or Mn 2+ for catalysis, but not Zn 2+ or Ca 2+ (Supplementary Figure S1). Although Mn 2+ can stimulate nuclease activity of NixI, work with other HNH nucleases, including a sequence specific nicking endonuclease (32), has shown that Mn 2+ can replace Mg 2+ , leading to non-specific activity (33,34). Therefore, we carried out our nuclease reactions in a buffer supplemented with 10mM Mg 2+ .…”
Section: Nuclease Assaysmentioning
confidence: 99%
“…The Gabija system is composed of the GajA and GajB proteins that contain ATPase, nuclease and helicase domains [ 73 , 94 ]. Gabija gives immunity to various phages when it was cloned in B. subtilis , and to phage T7 when it was cloned in E. coli [ 73 ].…”
Section: Resultsmentioning
confidence: 99%